Towards a Cognitively Informed Theory of Musical Rhythm: The Transformation of Thought about Rhythm in Tonal Music (Revista Argentina de Musicología, 2019)
The experience of music seems unequivocally related to the experience of time. And it is precisely in this time experience where the different dimensions of a phenomenon conventionally called musical rhythm are developed. The attempt to capture musical rhythm in its formal and operative aspects has represented both a theoretical challenge and a discussion with few agreements. Contemplating the latest ideas about rhythm in music, we observe that they have been directly or indirectly related to ideas close to musical cognitivism. A wide-scope vision is pursued in this work where the conceptual transformation of rhythmic thought in the tonal music of the common practice period is reviewed. Assumptions and problems are here presented, giving rise to reflections on the subject and on conceptual tools that allow us to think the space of theoretical research. We discuss the aspects that will be considered central in the construction of our proposal, to be developed in future contributions
Keywords: musical theory; musical cognition; musical rhythm; musical meter